The Effect of Implementing the Problem Based Learning (PBL) Learning Model on Student Learning Outcomes - Nuning Triana; Ismail, Ismail; Suryani, Andi Irma (PT. Ininnawa Paramacitra Edukasi, 2025)
Schools in Indonesia generally use conventional or traditional learning models, where teaching is still centered around the teacher as the main source of knowledge, while students play a more passive role as recipients of information. The lack of active interaction and student engagement in learning can lead to boredom and a lack of motivation to learn, which can result in lower student achievement. The objective of this study is to determine the effect of implementing the Problem-Based Learning (PBL) model on students' learning outcomes, conducted in Class X at SMA Negeri 8 Makassar on the topic of biotechnology. This research is an experimental study with two independent classes: a control class and an experimental class. Based on the research results and data analysis using SPSS statistics, and hypothesis testing using the Mann-Whitney test, an Asymp. Sig. (2-tailed) value of 0.004 was found. This shows that the Asymp. Sig. (2-tailed) value is less than 0.05, thus Hypothesis 1 is accepted. Therefore, it can be concluded that there is a significant effect of using the Problem-Based Learning model on the learning outcomes of students in Class X at SMA Negeri 8 Makassar, particularly on the topic of biotechnology